ASSESSMENT OF GENETIC DIVERSITY OF LUFFA GERMPLASM (Luffa cylindrica (L.) Roem) USING RAPD MARKER - Hải, Trương Thị Hồng; Ngà, Trần Bảo (Hue University Journal of Science: Natural Science, 2018)
In this study, 11 RAPD polymorphic primers selected from 100 primers were used to study the genetic diversity of 48 Luffa cylindrica (L.) Roem accessions, 47 of which were collected from The Plant Resource Center – Vietnam Academy of Science, and one local variety was collected in Gia Lam – Hanoi. Based on the degree of the coefficient of genetic similarity, 48 varieties were classified into seven major groups. Group I consisted of 18 varieties with the coefficient of genetic similarities ranging from 0.62 to 0.69 and divided into two subgroups. Group II consisted of 8 varieties and divided into 2 sub-groups. Group III had 11 varieties with the highest genetic correlation coefficient of 0.83. Group IV included 3 varieties with a coefficient of 0.73. Group V composed three varieties with the similar coefficients ranging from 0.67 to 0.7. Group VI included three varieties with the similarity coefficient of 0.76. Group VII included 2 varieties with the coefficient of 0.54. The genetic diversity of the Luffa germplasm will enable breeders to select hybrid combinations having superior hybrids to serve subsequent studies of trait heredity and breeding program.